Enigmatic ribbon-like fossil from Early Cambrian of Yunnan, China - Feng Tang; Si-cun Song; Guang-xu Zhang; Ai-lin Chen; Jun-ping Liu (China Geology, 2021)
During the Late Neoproterozoic and Early Cambrian, a series of paleogeographic and paleoecological events occurred associated with deglaciations and the evolution of life. The appearance of fossils representing diverse phyla, novel body plans and complex ecologies in Ediacaran and Cambrian sedimentary successions has sparked diverse hypotheses about potential drivers for the radiation of early animals during this interval. Recently, new macroscopic fossils of carbonaceous compressions with unique features have been found in Anning, Yunnan, China. The fossils’ bodies are ribbon-shaped and bilaterally symmetric, with dense longitudinal features and transversal features. The fossils occur 0.68 m below a bentonite interlayer which has been dated 535.2 ± 1.7 Ma by Ri-xiang Zhu and his team in 2009. The relatively simply morphology of these fossils, coupled with a lack of preserved internal structures challenge efforts taxonomically identify the precursor organism and definitively ally it to a living group. However, the symmetry and unusual features of the body are analogous to members of Platyzoa. The presence of ribbon-shaped fossils in the Zhongyicun Member in Anning indicates that these organisms were at least a locally significant component of Cambrian seafloor ecosystems, and may hold important implications for our understanding of the early evolution of Bilateria.